KAJIAN TEOLOGI PADA UPACARA KEMATIAN DI BALI: ANALISIS TEKS DAN KONTEKS - Harsananda, Hari; Saitya, Ida Bagus Subrahmaniam (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This paper discusses the theological dimensions of the Ngaben death ritual in Bali, focusing on the relationship between Hindu concepts of divinity as outlined in Tattwa texts and the implementation of death rituals. In Hindu theology, the understanding of Brahman, both in its Nirguna (without attributes) and Saguna (with attributes) forms, plays a significant role in shaping the spiritual goals of Balinese Hindus related to eschatology and the attainment of moksha. This research uses a qualitative method with a theological approach. Through an analysis of texts such as Yama Purana Tattwa and Wrhaspati Tattwa, this article examines the meaning and purpose of Ngaben as a ritual for purifying the soul and releasing material elements. This research finds that, although there is a hope for the unification of the soul with God (moksha), the practice of Ngaben is more focused on Bhakti and Karma Marga, which emphasize the existential duality between atman (individual soul) and Brahman, in accordance with the Dvaita Vedanta approach. This indicates a difference between the theological concept of union with God in moksha and its implementation in death rituals in Bali about the importance of the results or conclusions brief.